Pelatihan Inovasi Pemanfaatan Hasil Laut Menjadi Abon dan Kerupuk Ikan Desa Labu Ijuk Kabupaten Sumbawa - Shafwan Amrullah; Devi Tanggasari; Ariskanopitasari Ariskanopitasari; Lalu Heri Rizaldi; Mikhratunnisa Mikhratunnisa; Adi Ardiansyah (BADAN PENERBIT STIEPARI PRESS, 2023)
The use of marine products in almost all coastal locations in Indonesia has stagnated in selling value. This is because people in Indonesia have not processed marine products properly. One location that has problems like this is in Labu Ijuk, in the District of Moyo Hilir, Sumbawa Regency. In this activity, Lecturers from the Agricultural Industrial Technology Study Program, Sumbawa University of Technology (TIP-UTS) conducted training for the local community, especially those who work as fishermen. The training carried out was in the form of training in making floss and crackers from the basic ingredients of fish caught by local fishermen. The type of fish used is flying fish with the Latin name Decapterus. This fish is very abundant. After that, the material was given directly by the TIP-UTS Lecturer. The results of this service produce fish floss and fish crackers which must be dried in the sun first. After production was carried out, the team agreed with the community to develop packaging types and marketing methods using several online platforms.